Linfomas de células T/NK das regiões oral e maxilofacial: um estudo multicêntrico - Thamiris de Castro Abrantes da Silva (2022)
Lymphomas represent an important, complex, and heterogeneous group of malignant proliferative disorders arising from lymphoid tissue cells. Mature T/NK cell lymphomas represent 12.7% to 26.2% of non-Hodgkin lymphomas, are relatively rare conditions, and the incidence of most neoplasms increases with age. Therefore, the aim of this study is to evaluate the clinicopathological and immunohistochemical characteristics of a series of mature T/NK cell lymphomas that affect the oral and maxillofacial regions and to provide an updated review of the literature on the biological basis of this group of malignancies. Cases diagnosed as mature T/NK cell lymphomas affecting the oral and maxillofacial region were retrospectively retrieved from six oral and maxillofacial pathology centers, and their diagnoses were confirmed by hematoxylin-and-eosin- stained slides, immunohistochemical reactions, and in situ hybridization for detection of Epstein-Barr virus (EBV). A total of 22 cases were included in this study. Eleven (50%) consisted of extranodal T/NK cell lymphomas, nasal type; eight (36.4%) were peripheral T-cell lymphomas, not otherwise specified; two (9.1%) were T-cell leukemia/lymphomas, adult type and one (4.5%) was an ALK-positive anaplastic large cell lymphoma. Overall, there was a predominance of males, with a mean age of 55 years. The palate was the most affected site (50%), and the tumors usually presented as destructive and painful ulcers. EBV was present in all cases of nasal type extranodal T/NK cell lymphoma but was absent in the other subtypes.